A sociodemographic, anthropometric and lifestyle‐based prediction score for screening children with overweight and obesity for hepatic steatosis: The HEPAKID index. Issue 8 (5th January 2021) - Oses, Maddi; Medrano, María; Galbete, Arkaitz; Arenaza, Lide; Ruiz, Jonatan R.; Sánchez‐Valverde, Felix; Ortega, Francisco B.; Labayen, Idoia
Summary: Background: Hepatic steatosis (HS) is currently the most prevalent hepatic disease in paediatric population and a major risk factor for type 2 diabetes and cardiovascular diseases. The proper identification of children with HS is therefore of great public health interest. Objective: To develop a new prediction score using anthropometric, sociodemographic and lifestyle factors to identify children with HS (the HEPAKID index). Previously published biochemical paediatric screening tools were validated in the same cohort. Methods: A total of 115 pre‐adolescent children aged 8 to 12 years with overweight/obesity, recruited at hospital paediatric units were enrolled in this cross‐sectional study. HS (≥5.5% hepatic fat) was assessed by magnetic resonance imaging (MRI). Anthropometric, sociodemographic and lifestyle variables were collected by validated tests/questionnaires. Results: Forty‐one children had MRI‐diagnosed HS (35.6%, 49% girls). These children had ( P  < .01) a higher waist‐height ratio, a lower cardiorespiratory fitness, a younger gestational age, and consumed more sugar‐sweetened beverages than their HS‐free peers. Children with HS were more likely to belong to an ethnic minority ( P  < .01) and to spend longer viewing screens than recommended ( P  < .05). The addition of these variables to the multivariate logistic regression model afforded a HEPAKID index with high discriminatory capacity (area under the receiver‐operating characteristic curve: 0.808, 95% CI 0.715‐0.901), and score of ≥25.0 was associated with high sensitivity (82%, 95% CI 68%‐96%). Biochemical biomarker‐based paediatric tools for identifying HS showed only moderate discriminatory capacity and low sensitivity (5%‐41%) in this cohort. Conclusions: The HEPAKID index is the first simple, non‐invasive, sensitive, inexpensive and easy‐to‐perform screening that can identify children with overweight or obesity who have HS.